Gender and Economic Adjustment in Sub-Saharan Africa - Grieco, Margaret (World Bank, Washington, DC, 2012)
Gender bias, or "neutrality" in the underlying concepts, and tools of economics, has led to "invisibility" of women's economic, and non-economic work, thus, to an incomplete picture of total economic activity. This is predominantly so in Africa, where women articulated their concern regarding the social costs of adjustment, and the impact of adjustment on women. This drove to consolidating the adjustment experience with documented findings on the effects of structural adjustment, and to address the absence of attention to gender in up-stream macroeconomic analysis, and policy formulation, which are at the core of designing adjustment programs, and sectoral strategies. The note reviews the implications, or lack thereof, in considering gender as a distinguishing factor in the design of economic adjustment measures, whose analysis suggests that the improvement in the content of adjustment to include social dimensions, still has to go farther in incorporating gender concerns. In moving toward action in adjustment, it is critical that local, and international capacity be built to undertake relevant gender analysis, focusing among others, on the gender-exclusionary bias of economic, and financial services, such as agricultural research and extension, and enterprise credit. Moreover, public expenditure analysis could provide the basis for an integrated policy, where the inclusion of gender-focused projects in the expenditure program is recommended, as a means of removing constraints limiting women's response to improved policy.